Directional fluorescence emission from a compact plasmonic‐diamond hybrid nanostructure. Issue 4 (11th May 2016) - Shen, Hongming; Chou, R. Y.; Hui, Yuen Yung; He, Yingbo; Cheng, Yuqing; Chang, Huan‐Cheng; Tong, Limin; Gong, Qihuang; Lu, Guowei
Abstract : Unidirectional emission from a fluorescent nanodiamond is achieved in an experiment by coupling it to a single gold nanorod as an ultracompact antenna. Abstract: Ultracompact directional optical nanoantennas are rapidly gaining popularity yet still challenging tasks to construct at the nanoscale. Here, we experimentally demonstrate unidirectional emission from a fluorescent nanodiamond coupled with a single gold nanorod. Different configurations of the assembled hybrid nanostructures were realized via step‐by‐step atomic force microscope nanomanipulation. The emission patterns can be controlled by adjusting the configurations, i.e., the gold nanorod orientation and separation with respect to the nanodiamond. Numerical simulation results reveal that the unidirectional emission can be ascribed to the interference between the electromagnetic fields produced by the dipole‐like source and the out‐of‐phase dipole induced in the gold nanorod. The proposed hybrid nanostructures remarkably exhibit highly unidirectional emission even when the emitter is positioned up to 50 nm away from the nanorod antenna and present a broad working spectral bandwidth of ∼200 nm. The distinct features of this hybrid structure suggest potential applications for novel nanoscale light sources, sensing, and quantum information.